Komparasi Penafsiran Ibn Kathīr dan Amina Wadud tentang Hak Waris Laki-laki dan Perempuan - Nidaul Islam; Muhammad Patri Arifin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
This article aims to examine the similarities and differences in Ibn Kathīr and Amina Wadud’s interpretations of inheritance rights between women and men using a muqarran interpretation approach. Ibn Kathīr as an interpreter of mutaqaddimin and Amina Wadud are Muslim feminists who are critical of the issue of women’s rights, especially inheritance rights in Islam. In the Qur’an surah al-Nisā’ [4]: 11-12, Ibn Kathīr interprets that the share of a son is the same as that of two daughters and the remaining third of the inheritance becomes a mandatory will. Meanwhile, Amina believes that women have equal inheritance rights to men. The distribution of inheritance between men and women must comply with the principles of benefit and justice. In addition, without any restrictions on which heirs, the remaining third of the wealth can be inherited without reducing the distribution of the remaining wealth. This rule is quite flexible, and the most important thing is to fulfill the principle of justice.